2015
DOI: 10.5539/jas.v7n10p225
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Categorization of Some Water Yam (Dioscorea alata L.) Germplasm in Ghana Using Microsatellite (SSR) Markers

Abstract: The yam species, Dioscorea alata has an advantage for sustainable cultivation due to its comparatively good agronomic characteristics. Breeders are therefore keen to improve the food quality of the species. Nevertheless, published data on molecular classification and genetic diversity of this crop are scanty. This research therefore investigated genetic variability and relationships among some collected Ghanaian D. alata accessions (35) together with 14 introductions from IITA in Nigeria. The true genetic iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(21 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…Finally, high levels of genetic diversity using ISSR markers were also reported by Nascimento et al (2013) and Kung et al (2016). Other studies using SSR (Otoo et al, 2015;Arnau et al, 2017;Mulualem et al, 2018) and AFLP markers (Rivera-Jiménez et al, 2011) also reported high genetic diversity in yam.…”
Section: Genetic Diversitymentioning
confidence: 56%
“…Finally, high levels of genetic diversity using ISSR markers were also reported by Nascimento et al (2013) and Kung et al (2016). Other studies using SSR (Otoo et al, 2015;Arnau et al, 2017;Mulualem et al, 2018) and AFLP markers (Rivera-Jiménez et al, 2011) also reported high genetic diversity in yam.…”
Section: Genetic Diversitymentioning
confidence: 56%
“…alata using microsatellite markers. Several other studies on genetic diversity have been conducted on this species using different types of molecular markers including random amplified polymorphism DNAs [30, 55], amplified fragment length polymorphisms [15, 56, 57] and simple sequence repeat (SSR) markers [34, 58]. However, these included accessions from only one or two regions or collections.…”
Section: Discussionmentioning
confidence: 99%
“…alata collections, including RAPDs [30], AFLPs [31] and SSRs [32, 33, 34]. SSR markers (microsatellites) are considered to be the markers of choice for analyzing genetic diversity because of their co-dominance, high reproducibility, high global mutation rates and polymorphism [35, 36].…”
Section: Introductionmentioning
confidence: 99%
“…Molecular markers have been used to characterize D. alata diversity: random amplified polymorphic DNA (RAPD; Asemota, Ramser, Lopez-Peralta, Weising, & Kahl, 1996), isoenzymes (Lebot et al, 1998), amplified fragment length polymorphism (AFLP; Malapa, Arnau, Noyer, & Lebot, 2005), simple sequence repeats (SSRs; Siqueira, Marconi, Bonatelli, Zucchi, & Veasey, 2011;Sartie, Asiedu, & Franco, 2012;Otoo, Anokye, Asare, & Telleh, 2015;Chaïr et al, 2016;Arnau et al, 2017), plastid sequences , and Diversity Arrays Technology (DArT; Vandenbroucke et al, 2016).…”
Section: Introductionmentioning
confidence: 99%